Pengamatan Cara Belajar Siswa di SLB C Karya Tulus - Gultom, Meliana; Pianda, Lide Dudura; Manurung, Trinita; Sinuraya, Septeti; Tambunan, Yesa Anaria (Lumbung Pare Cendekia, 2024)
Special Schools (SLB) are educational institutions specifically designed to meet the educational needs of children with special needs. SLB provides educational services tailored to the physical, mental, and social needs of students with various types of disabilities, such as deaf, blind, mentally retarded, physically disabled, and autism. In SLB, teaching methods, curriculum, and facilities are designed so that children can develop optimally according to their respective potentials. SLB plays a role in shaping character, improving skills, and providing basic academic skills to students so that they are able to be independent and adapt in the social environment. With an inclusive and student-centered approach, SLB also helps reduce social barriers experienced by children with special needs, so that they can live equally and participate in society.